Quality assessment of Chinese preschools : developing a culturally relevant measure - Li, Kejian, 1975- (New York : Routledge, 2024)
"This book presents the development of the Chinese Early Childhood Environment Rating Scale (CECERS), a culturally appropriate tool for assessing the quality of Chinese preschools. It provides insights into the developmental profile and pedagogical characteristics of Chinese preschools, which have been the main type of children's services in China over the past three decades. The conceptual framework of CECERS is based on cultural contexts and refers to ECERS, an international quality assessment tool for early childhood education (ECE), and combines the essential elements of ECE quality (e.g. teacher-child interactions) with additional components tailored to the situation of Chinese preschools (e.g. group educational activities). A series of studies involving over 200 preschools and 500 classrooms were conducted to ensure the validity and reliability of the CECERS in different areas of China. The content of CECERS has been continuously adapted according to the results of these verification studies. The author also discusses issues related to improving the quality of Chinese preschools and proposes relevant policy recommendations. The book will be an essential read to students and scholars of educational theory and Chinese studies. It will also serve as an interesting reference for cross-cultural scholars in the field of ECE research"--
Introduction to Chinese preschools -- Preschool quality and child development -- Constructing the concept of quality for Chinese preschools: A crosscultural perspective -- Developing a measurement tool for the evaluation of Chinese preschool quality-CECERS (trial version) -- Measurement reliability of CECERS-trial: Analysis based on Multivariate Generalizability Theory and Item Response Theory -- Continuous improvement and verification of the CECERS -- Assessing preschool quality in China using CECERS.
Keywords: Early childhood education -- China; Education, Preschool -- China -- Evaluation; Schools -- Ratings and rankings -- China; Educational evaluation -- China; Culturally relevant pedagogy -- China; EDUCATION / Evaluation; EDUCATION / Preschool & Kindergarten; EDUCATION / General